Pembangunan Sistem Informasi Pendataan Rumah Tangga Miskin Kecamatan Tulakan Kabupaten Pacitan - Mustikowati, Dyah Ayu (Speed - Sentra Penelitian Engineering dan Edukasi, 2013)
ABSTRACT: Activity Management Unit of Poor Households Tulakan District is a government agency tasked to collect data on poor households, with the existence of these governmental agencies will be helped to find the data of poor households. So far, data management still done conventionally, allowing the damage intentionally or unintentionally, and that data can be manipulated. In addition to the search for the data takes a long time. With this praktikan providing information systems solutions making the data collection of poor households. Which aims to produce a collection of information systems of poor households based computer that can assist the process of data collection reporting to the leadership of poor households are more accurate and more timely as expected and diiginkan by the user or the user. The method used in the manufacturing information system is a collection of poor households observation method, interview method. While the development of a conceptual information system is a system analysis, system design, programming, testing programs, implementation of the program. Information systems data collection of poor households is built using Microsoft Visual Basic 6.0 with Microsoft Access databases supported. With a system of collection of information is of poor households, is expected to help the process of data collection reports to the leadership of poor households. Keywords: Data Collection Information Systems of Poor Households ABSTRAKSI: Unit Pengelola Kegiatan Rumah Tangga Miskin Kecamatan Tulakan adalah sebuah instansi pemerintah yang bertugas melakukan pendataan rumah tangga miskin, sistem manualnya dirasakan tidak lagi memadai untuk penaganan beban kerja, khususnya pendataan rumah tangga miskin. Keadaan demikian menuntut penggunaan sistem informasi berbasis teknologi komputer. Sistem informasi ini penulis namakan sebagai Sistem Informasi Rumah Tangga Miskin yang meliputi Sistem Informasi Data Penduduk, Sistem Informasi Data Penduduk Miskin dan Sistem Informasi Analisis Penduduk Miskin. Penelitian ini bertujuan untuk merancang sistem informasi pendataan rumah tangga miskin yang terkomputerisasi. Metode yang digunakan dalam pembuatan sistem informasi pendataan rumah tangga miskin adalah metode observasi, metode wawancara. Sedangkan pengembangan sistem informasi secara konseptual adalah analisis sistem, perancangan sistem, pembuatan program, pengujian program, implementasi program. Sistem informasi pendataan rumah tangga miskin ini dibangun dengan menggunakan bahasa pemrograman Microsoft Visual Basic 6.0 dengan didukung basis data Microsoft Acces. Dengan adanya sistem informasi pendataan rumah tangga miskin ini, diharapkan dapat membantu dalam melakukan kegiatan kesejahteraan sosial khususnya dan Kecamatan Tulakan umumnya.. Kata Kunci     : Sistem Informasi Pendataan Rumah Tangga Miskin